2019
DOI: 10.1186/s12957-019-1701-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of three-dimensional reconstruction in laparoscopic partial nephrectomy for complex renal tumors

Abstract: Background To evaluate the role of three-dimensional (3D) reconstruction technique in renal function protection and ipsilateral parenchymal mass preserved after laparoscopic partial nephrectomy (LPN) in patients with complex renal tumor (R.E.N.A.L.score ≥ 8). Methods A retrospective study enrolling 49 patients who suffered from RCC and underwent LPN at our center, from October 1, 2017, to October 31, 2018. Twenty-one patients (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…To reduce the pooled result of heterogeneity, we consecutively omitted the included studies individually. After Wang et al's study (14) was excluded, the heterogeneity of the intraoperative blood loss declined (SMD = −0.29; 95% CI = −0.46 to −0.13, I 2 = 49.8%, P = 0.044; Figure 4C).…”
Section: Subgroup Analysismentioning
confidence: 98%
See 4 more Smart Citations
“…To reduce the pooled result of heterogeneity, we consecutively omitted the included studies individually. After Wang et al's study (14) was excluded, the heterogeneity of the intraoperative blood loss declined (SMD = −0.29; 95% CI = −0.46 to −0.13, I 2 = 49.8%, P = 0.044; Figure 4C).…”
Section: Subgroup Analysismentioning
confidence: 98%
“…The basic characteristics of all 10 included studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were summarized and are shown in Table 1. All studies were published between 2017 and 2020.…”
Section: Characteristics and Qualifications Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations